Development of self-contained microelectrochemical bioassay platforms for small volumes - Aguilar, Zoraida P.; Fritsch, Ingrid (ProQuest Dissertations & Theses Global, 2002)
"This dissertation presents studies performed toward the development of self-contained microelectrochemical bioassay platforms for small volumes. These studies were necessary to characterize surface modification processes, establish limits of detection and sensitivity, characterize materials for immobilzing biomolecules, and investigate magnetohydrodynamics effects on small volumes and on microfluidic systems. The self-contained microelectrochemical device described permitted chemical sensing for small volumes with zeptomole detection limits. The layering fabrication method allows electrodes to be constructed within short distances of each other that remain individually addressable. The bioassay components are located closely to other electrodes so that detection occurs separately from the modified surface in a concentrated region of enzymatically-generated products, resulting in stability, high signal, and rapid assay. Mouse IgG is used as model analyte for the self-contained microelectrochemical assay for small volumes. The features of the mouse IgG immunoassay are applied toward the development of Au-coated silicon wafer based bioassay platforms to detect Cryptosporidium parvum. An enzyme linked immunoassay for the oocysts and a DNA-hybridization assay for C. parvum hsp70 mRNA were developed using alkaline phosphatase label on the secondary probe. The electrochemical DNA hybridization detection of hsp70 mRNA took 15 h to complete and shows no cross reactivity to C. muris, and other water pathogens. Studies using Au-screen printed low temperature co-fired ceramic materials as platform for mouse IgG immunoassay was demonstrated. The preliminary studies show promising results for the development of micrototal analysis systems. Finally, magnetohydrodynamics (MHD) for the amplification of electrochemical signal is reported. The presence of a magnetic field in a CV setup of ferricyanide solution using TNB microelectrode from a 50-mum diameter cavity as working electrode in an internal setup showed maximum effect at perpendicular orientations between the direction of the current and the magnetic field, as expected, and were similar in bulk solution down to volumes as small as ∼1 nL. MHD effects on the currents from a 50:50 molar ratio of 0.6 M K3Fe(CN) 6 and 0. 6 M K4Fe(CN)6 in 0.1 M KCl using macro electrodes in an open beaker setup and in a channel showed similar trends as those using microelectrodes. The MHD amplifications of currents from these studies are important in developing microchip microfluidic devices for the analysis of small volumes."--Abstract.
Thesis (PhD)--University of Arkansas, Fayetteville, 2002
Includes bibliographical references.
Keywords: Biological assay; Biological assay -- Statistical methods; Electronic book